FALKO DAIM/KURT GSCHWANTLER/GEORG PLATTNER/PETER STADLER (HRSG/EDS), DER GOLDSCHATZ VON SÂNNICOLAU MARE (UNGARISCH: NAGYSZENTMIKLÓS) / THE TREASURE OF SÂNNICOLAU MARE (HUNGARIAN: NAGYSZENTMIKLÓS) (JOURNAL OF ANCIENT HISTORY AND ARCHAEOLOGY, 2016)
Falko Daim/Kurt Gschwantler/Georg Plattner/Peter Stadler (Hrsg/eds), Der Goldschatz von Sânnicolau Mare (Ungarisch: Nagyszentmiklós) / The treasure of Sânnicolau Mare (Hungarian: Nagyszentmiklós), Verlag des Römisch-Germanischen Zentralmuseums, RGZM Tagungen Band 25,Mainz 2015, 164 p.